Advertising Ethics: A Quranic Perspective - Mohammad Noorizzuddin Nooh; Syadiyah Abdul Shukor; Khairil Faizal Khairi; Muhammad Ridhwan Ab. Aziz; Mahdhir Abdullah; Rozaimie Abdul Rahman (International Journal of Liberal Arts and Social Science, 2024)
Volume: 2 No: 5 (page: 77-82)